Unsettling Experience, Perception, and Display. Issue 1 (1st June 2019) - Neely, Sol
Abstract : This Screen Shot section includes three texts—an interview and two articles—that, together, occasion an unsettling movement in the development of an Indigenous phenomenology staged upon Screen Bodies' concern for the critical tryptic experience, perception, and display. Such phenomenology, moreover, takes shape in the spirit of an enduring and persistent Indigenous cosmopolitanism, one organized by an appeal to a pan-tribal solidarity that is also not shy about drawing from efficacious sources of critique internal to European critical traditions. Together, these texts—and the source materials that inspire them—build rich ecumenical perspectives in the service of decolonial justice and pedagogy. And while the texts included here are composed in English, each draws from and references Indigenous languages, articulating one kind of Indigenous cosmopolitanism that makes use of English as a kind of "trade language." To stage an Indigenous phenomenology by appeal to an Indigenous cosmopolitanism, in our contemporary political moment, thus calls for critical attention attuned to the perspectives, traditions, and imaginations of what Tlingit poet and author Ernestine Hayes describes as "Indigenous intellectual authority." In this spirit, Indigenous cosmopolitanism occasions a decolonial-critical cosmopolitanism rooted not in the secular, Habermasian cosmopolitanism of Europe but in the modalities of consciousness, the literary genius and acumen, of Indigenous oral literary traditions. In the context of such a cosmopolitanism in which everyone is variably situated, across the spectrum that divides descendants of perpetrators and victims of settler colonialism, the critical imperative becomes a decolonial one, and non-Indigenous readers are called to shed the epistemological, ontological, and political priorities that broadly characterize European analytical and continental traditions, whatever their internal debates may be. Such an imperative forces phenomenological attention not only on the macrological instantiations of settler-colonial power but also against the "micrological textures of power" that ultimately shape the inner contours of self and, thus, what becomes phenomenologically legible to individuals situated in their cultural contexts.